2022
DOI: 10.1111/den.14224
|View full text |Cite
|
Sign up to set email alerts
|

Management of non‐functional pancreatic neuroendocrine tumors by endoscopic ultrasound‐guided radiofrequency ablation: Retrospective study in two tertiary centers

Abstract: Background: Recently, there has been growing interest in investigating endoscopic ultrasound-guided radiofrequency ablation (EUS-RFA) for the management of small nonfunctional pancreatic neuroendocrine tumors (nf pNETs). Patients and Methods:A bicentric retrospective study was performed that included patients with histologically confirmed nf pNETs who were consecutively treated by EUS-RFA between December 2015 and March 2021 at two tertiary referral centers. Results:In 27 patients (mean age 65.0 years, 52% mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Additionally, Marx et al [ 31 ] reported two recent trials. The first study included 7 patients with insulinoma, with a complete resolution rate reported in 6 patients (85.7%).…”
Section: Eus-rfa In Pnensmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Marx et al [ 31 ] reported two recent trials. The first study included 7 patients with insulinoma, with a complete resolution rate reported in 6 patients (85.7%).…”
Section: Eus-rfa In Pnensmentioning
confidence: 99%
“…Twenty-five patients (92.6%) had a complete radiological resolution at a mean follow-up time of 15.7 mo (range 2-41). Notably, procedure-related AEs occurred in 9 patients[ 31 ] (Table 1 ).…”
Section: Eus-rfa In Pnensmentioning
confidence: 99%
“…The mechanism of action of RFA is high‐frequency alternating current, generating high local temperatures that induce coagulative necrosis of the tissues 44 . This treatment approach has been proposed for pancreatic solid lesions, such as PC, NEN, SPN, and other malignant metastatic lesions; 7–21,45,46 however, only the feasibility and safety for treating for PC were assessed. Two ablation devices specifically designed for EUS are mainly used.…”
Section: Summary Of Reviewed Studiesmentioning
confidence: 99%
“…
We thank Dr Rimbas and his colleagues for their interest in our case series on endoscopic ultrasound-guided radiofrequency ablation (EUS-RFA) of nonfunctional pancreatic neuroendocrine tumors (NFpNETs) ≤2 cm in 27 patients. 1 Regarding the rate of complications, Rimbas and colleagues questioned whether EUS-RFA treatment was justified in lesions with a size of 9-10 mm. Adverse events occurred during the first nine procedures.
…”
mentioning
confidence: 99%